Role of CXCR3/CXCL10 Axis in Immune Cell Recruitment into the Small Intestine in Celiac Disease - Bondar, Constanza María (2014)
Lymphocytic infiltration in the lamina propria (LP), which is primarily composed of CD4+ Th1 cells and plasma cells, and increased numbers of intraepithelial lymphocytes (IELs), is a characteristic finding in active Celiac Disease (CD). Signals for this selective cell recruitment have not been fully established. CXCR3 and its ligands, particularly CXCL10, were suggested to be one of the most relevant pathways in attracting cells into inflamed tissues. In addition, CXCR3 is characteristically expressed by Th1 cells. The aim of this work was to investigate the participation of the chemokine CXCL10/CXCR3 axis in CD pathogenesis. A higher concentration of CXCL10 was found in the serum from untreated CD patients. mRNA levels for CXCL10 and CXCL11 but not CXCL9 were significantly higher in duodenal biopsies from untreated CD patients compared with non-CD controls or treated patients. CXCL10 was observed to be abundantly produced in untreated CD; the expression of CXCL10 correlated with IFN levels in the tissue and was reduced in treated patients. Plasma cells and enterocytes were identified as CXCL10 producer cells. Moreover, CXCL10 expression in intestinal tissues was upregulated by poly I:C or IL-15. IELs, LP T lymphocytes, and plasma cells, which infiltrate major populations in intestinal mucosa in untreated CD, express CXCR3. The CXCR3/CXCL10 signalling axis is overactivated in the intestinal mucosa in untreated patients, which explains the specific recruitment of the major cell populations that infiltrate the epithelium, as well as the LP, in CD.